Effectiveness of exercise programs to reduce falls in older people with dementia living in the community: A systematic review and meta-analysis - Burton, Elissa; Cavalheri, Vinicius; Adams, R.; Browne, C.; Bovery-Spencer, P.; Fenton, A.; Campbell, B.; Hill, Keith (Dove Medical Press, 2015)
Objective: The objective of this systematic review and meta-analysis is to evaluate the effectiveness of exercise programs to reduce falls in older people with dementia who are living in the community. Method: Peer-reviewed articles (randomized controlled trials [RCTs] and quasi-experimental trials) published in English between January 2000 and February 2014, retrieved from six electronic databases – Medline (ProQuest), CINAHL, PubMed, PsycInfo, EMBASE and Scopus – according to predefined inclusion criteria were included. Where possible, results were pooled and meta-analysis was conducted. Results: Four articles (three RCT and one single-group pre- and post-test pilot study) were included. The study quality of the three RCTs was high; however, measurement outcomes, interventions, and follow-up time periods differed across studies. On completion of the intervention period, the mean number of falls was lower in the exercise group compared to the control group (mean difference [MD] [95% confidence interval CI] =-1.06 [-1.67 to -0.46] falls). Importantly, the exercise intervention reduced the risk of being a faller by 32% (risk ratio [95% CI] =0.68 [0.55–0.85]). Only two other outcomes were reported in two or more of the studies (step test and physiological profile assessment). No between-group differences were observed in the results of the step test (number of steps) (MD [95% CI] =0.51 [-1.77 to 2.78]) or the physiological profile assessment (MD [95% CI] =-0.10 [-0.62 to 0.42]).Conclusion: Findings from this review suggest that an exercise program may potentially assist in preventing falls of older people with dementia living in the community. However, further research is needed with studies using larger sample sizes, standardized measurement outcomes, and longer follow-up periods, to inform evidence-based recommendations.